Utilization of Spirulina Sp. Microalgae for Oxygen Production - Mohammad Erlangga; Adian Khoironi; Oki Setiono (Journal of Bioresources and Environmental Sciences, 2026)
Global warming, largely driven by rising CO₂ levels, poses a serious environmental threat. Meanwhile, the decline of green spaces, especially in cities, reduces natural CO₂ absorption. In response to this issue, this true experimental research introduced an innovative approach called Smart Microalgae Reactor, which utilizes Spirulina Sp. as an alternative CO₂ absorber to produce oxygen. This study aimed to evaluate the effectiveness of microalgae Spirulina Sp. in capturing CO₂ through three experimental setups: Reactor 1 (2000 mL Spirulina Sp.+ 2 L/min CO₂), Reactor 2 (1500 mL + 2 L/min CO₂), and a Control (2000 mL, no CO₂). CO₂ was injected daily for 1 minute, and key parameters Dissolved Oxygen (DO), Optical Density (OD), and growth rate (μ) were measured over 13 days. The results showed Reactor 2 had the highest DO increase (12.6 mg/L, 63.64%) and fastest early growth (0.0904 day⁻¹), while Reactor 1 achieved the highest OD (1.550, 111.48%) but slower growth. The control performed weakest, confirming that added CO₂ boosts photosynthesis. The study proves that smart microalgae reactor is an effective, sustainable solution for urban CO₂ reduction, offering a viable alternative where traditional greenery is limited.